Alcohol and Other Drug (AOD) Education for Hospital Staff: An Integrative Literature Review. (2nd January 2017) - Brereton, Rebecca; Gerdtz, Marie
Abstract : Alcohol and Other Drug (AOD) education amongst hospital staff is often inadequate. This leads to suboptimal care of patients and is a missed opportunity for early identification and treatment. This integrative review evaluates the core features of current education for hospital-based doctors and nurses in AOD, including country of origin, content, duration, and pedagogy. The majority of included studies were conducted in the USA (72%), target alcohol rather than AOD in general (72%), adopted a purely medical model of treatment (94%), and utilised a Screening, Brief Intervention, and Referral to Treatment (SBIRT) model (94%). The overall quality of the studies was weak-moderate, which led to small effect sizes in most studies and limits the generalizability of any conclusions. More high quality research trials are needed to establish the core features of effective AOD education for hospital staff. Future research should include a focus on the psychosocial context of addiction, other drug use and the impact of negative attitudes on care delivery.